2007
DOI: 10.1007/s10725-006-9155-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of transplanted rice by seed priming

Abstract: Transplanting is the major method of rice cultivation in the world, in which seedlings are raised in nursery and then transplanted into well puddle and prepared fields. The traditional nursery sowing method is tedious and produces week seedlings that reduce the final yield due to high mortality. The potential of seed priming to improve the nursery seedlings and thus the transplanted rice was evaluated in the present study. The experiment was conducted in the rice growing area (31. 45°N, 73.26°E, and 193 m) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 15 publications
3
57
1
2
Order By: Relevance
“…We did not see a strong effect of fertilizer management in contrast to Mishra and Salokhe, who observed that fertilizer application in the nursery was a crucial factor in increasing seedling vigor [31]. Similarly Farooq et al also found an increasing trend of plant height after transplanting improved nursery seedlings [32]. The fact that the wet conditions in 2010 obviously caused maximal height in all treatments indicates that nursery treatment might be more important in stress conditions.…”
Section: Plant Heightcontrasting
confidence: 74%
“…We did not see a strong effect of fertilizer management in contrast to Mishra and Salokhe, who observed that fertilizer application in the nursery was a crucial factor in increasing seedling vigor [31]. Similarly Farooq et al also found an increasing trend of plant height after transplanting improved nursery seedlings [32]. The fact that the wet conditions in 2010 obviously caused maximal height in all treatments indicates that nursery treatment might be more important in stress conditions.…”
Section: Plant Heightcontrasting
confidence: 74%
“…Seed priming in aerated solutions trigger metabolic activities which are essential for germination and improves uniformity, germination rate, final germination and stand establishment (Bradford, 1976;Afzal et al, 2016). Usually seed treatment is conducted in low water potential solution and incorporation of plant growth hormones for priming significantly improved the seed performance of several crops (Afzal et al, 2011) rice (Basra et al, 2006) and rice (Farooq et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…into the puddled field is widespread practice for rice growing which demands huge water and labor input throughout the crop season (Farooq et al, 2007).…”
Section: Conventionally Transplantation Of Nursery Seedlingsmentioning
confidence: 99%